Early Orientalism : Imagined Islam and the Notion of Sublime Power. - Kalmar, Ivan Davidson (Majmūʻah-ʼi ʻulūm va maʻārif-i Islāmī., 2012)
The history of western notions about Islam is of obvious scholarly as well as popular interest today. This book investigates Christian images of the Muslim Middle East, focusing on the period from the Renaissance to the Enlightenment, when the nature of divine as well as human power was under particularly intense debate in the West. Ivan Kalmar explores how the controversial notion of submission to ultimate authority has in the western world been discussed with reference to Islam's alleged recommendation to obey, unquestioningly, a merciless Allah in heaven and a despotic government on earth.